Fire detection from image and video using YOLOv5 - Wang Liao (Инноватика-2025 : сборник материалов XXI Международной школы-конференции студентов, аспирантов и молодых ученых, 28-30 апреля 2025 г., г. Томск, Россия)
In today's rapidly advancing era of technology, the potential of artificial intelligence (AI) has been harnessed across various domains, from autonomous vehicles to health diagnostics. One significant and innovative application of AI is in fire detection, a realm where timely and accurate detection can be a matter of life and death. Integrating AI into fire detection systems represents a significant leap from traditional methods, offering enhanced efficiency and reliability